Prehospital analgesic choice in injured patients does not impact on rates of vomiting: Experience from a New South Wales primary retrieval service. (4th December 2017) - Zhang, Michael; Cowan, Timothy; Smiles, John‐Paul; Morgan, Mary; Armstrong, Jessica; Goswami, Chinky; Sewell, Claire
Abstract: Objective: This study aimed to explore the analgesic regimes adopted in our contemporary retrieval practice and the incidence of vomiting in ED after prehospital analgesic use. Method: A retrospective review was conducted on trauma patients retrieved by the Hunter Primary Retrieval Service in the Hunter New England Local Health District, New South Wales, Australia, during 2015. Results: Of the 379 patients attended by the service in 2015, 196 of them (mean age 38.6, SD 19.68, years) were selected for this review. Morphine was the most commonly used analgesic (mean 68.37%; 95% CI 61.36–74.81%), followed by fentanyl (mean 48.47%; 95% CI 41.29–55.70%) and ketamine (mean 34.18%; 95% CI 27.57–41.28%). Fourteen (7.14%, 95% CI 3.96–11.69%) patients vomited either prehospital or within the ED. Patients in both the emesis and the non‐emesis group were comparable in demographics. None of the three studied analgesics were observed to be significantly associated with higher risk of vomiting than the others in this review, although a higher dose of fentanyl was given to the non‐emesis group ( P  = 0.04). Conclusions: The frequency of vomiting in the retrieved patients observed in our study was less than previously reported in the literature. Opioids still prevailed over ketamine as the preferred initial analgesic, with ketamine most commonly used as an adjunct. Multi‐centre trials in this field would be preferable in future in view of the relatively low incidence of vomiting in retrieved trauma patients.